Energy consumption, economic growth and pollution in Saudi Arabia - Haider Mahmood; Tarek Tawfik Yousef Alkhateeb; Maleeha Mohammed Zaaf Al-Qahtani; Zafrul Allam; Nawaz Ahmad and Maham Furqan (Management Science Letters, 2019)
Economic growth is very basic need of any economy but its environmental effects should not be ignored. We investigate the environmental effects of economic growth and energy consumption of Saudi Arabia. The study uses data of a period 1968-2014 and cointegration test and corroborates a long- and short-run relationships. The results indicate that economic growth and energy consumption contributes in CO2 emissions in both long- and short-run. It means that increasing economic growth of the Kingdom has social cost on the economy in terms of pollution emissions. Based on findings, we recommend to use the alternative renewable sources of energy consumption to avoid the pollution effects of growth in Saudi Arabia.